Optimization of hot water extraction for sapodilla juice using response surface methodology. - Sin, H. N.; Yusof, Salmah; Sheikh Abdul Hamid, Nazimah; Abd. Rahman, Rakmi (Elsevier, 2006)
A central composite design was employed to optimize the extraction conditions of sapodilla juice using hot water extraction. The independent variables were juice extraction time (30–120 min) and temperature (30–90 C). The combined effect of these variables on juice yield, odour, taste and astringency were investigated. Results showed that the generated regression models adequately explained the data variation and significantly represented the actual relationship between the independent variables and the responses. The results showed that extraction temperature was the most important factor affecting the juice characteristics as it exerted a significant influence on all the dependent variables. Higher temperature increased the juice yield, taste and odour but also showed an increase in astringency which affected the acceptability of the juice. The contour plots showed the relationships between the independent variables and the responses were developed. By superimposed of the contour plots, optimum condition of 60 C for 120 min was established for hot water extraction of sapodilla juice.